Assessing determinants of students’ achievement in senior secondary school biology (2018)
The study is a correlational research type. The sample for the study comprised 200 respondents from 5 public schools in Ibadan North West Local Government Area of Oyo State. Three instruments namely: Parental Role Scale (a =0.71), Grasha-Riechmann Student Learning Style Scale (a = 0.87) and Biology Achievement Test (KR20 = 0.88) were used to collect data from the respondents and data collected were analyzed using multiple regression analysis. Results indicated that a statistically significant linear relationship exists between the predictor variables (parental roles and students learning style) and the criterion variable (students’ academic achievement in biology). Parental roles accounted for 4.9% of the variance in students’ achievement in biology while learning styles account for 4% of the total variance observed in students’ achievement in biology. Based on the findings, it is recommended that parents should be deeply committed to activities that connect with the schooling process of their children to foster academic achievement.